The Frequency of Breast Cancer Among Women Referred to Hospitals for Biopsy in Birjand, Iran During 2011-2013 - Hoshyar, Reyhane; Haghighi, Fatemeh; Hosseinian, Mahdiyeh; Mezginejad, Fatemeh; Mollaei, Homa; Fakhr, Negar; Beyki, Zahra (Archives of Breast Cancer, 2016)
Background: This study aims to demonstrate the frequency of malignant breast cancer (BC) according to pathologic findings in Birjand during 2011-2013 years. Methods: For this cross-sectional study, the sample consisted of pathologic records from 229 breast biopsies of two hospitals in Birjand. Results: Most of the biopsies in women were malignant cases which nearly 90% of them were detected after lymph node involvement. The mean age of women with malignant BC was 48.8 years. Conclusions: A notable proportion of our cases were diagnosed in metastatic stages as advanced BC. It further highlights the importance of screening and diagnosis at earlier stages.